Injudicious Provision of Subtherapeutic Doses of Antibiotics in Community Pharmacies - Mohamed E Amin; Amira Amine; Mohammad Shoukry Newegy (University of Minnesota Libraries Publishing, 2017)
Background: Egyptian pharmacists routinely provide antibiotics without a prescription. A few pills of common cold products are offered under the name "cold group". A cold group may contain one or more pills of antibiotics. This study aimed to estimate the proportion of pharmacies that provide subtherapeutic doses of antibiotics in community pharmacies as part of a CG or upon direct request from a simulated client. Methods: A probability sample of community pharmacies in Alexandria, Egypt was selected. A simulated client approached pharmacy staff using a standardized scenario. He initially requested a cold group and followed by requesting two antibiotic pills. Results: The simulated client visited 104 pharmacies and was sold an antibiotic at 68 pharmacies in total. A cold group with one or more antibiotic pills was provided in 31 pharmacies. Upon request for two antibiotic pills, 2-8 antibiotic pills were provided in 30 pharmacies whereas an antibiotic carton was provided in three pharmacies. In four pharmacies, the simulated client was sold a cold group containing an antibiotic as well as another antibiotic upon request. Beta-lactam antibiotics comprised 76% of antibiotics provided. In five encounters, the simulated client was told that the cold group contained an antibiotic when, in fact, it did not. Conclusions: Subtherapeutic doses of antibiotics are provided at dangerous rates in Alexandria's community pharmacies. Interventions are urgently needed to tackle different factors contributing to this dangerous practice. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties   Type: Original Research